Pelatihan Teknologi Mesin Multifungsi, Pengupas, Perajang dan Pengering Nanas - Lizar,; Abdul Gafur, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The implementation of this Community Service Program aims to overcome the problems of the Tunas Harapan Baru Farmers Group in Penampi Village, where at this time, when harvest time arrives, many small pineapple fruits cannot be sold until they become rotten. Therefore, to overcome these problems, technology in the form of a pineapple peeler, chopper and dryer was created. This machine uses 3 electric motors which function as pengerak. The pineapple peeler uses a 1.5HP electric motor while the pineapple chopper and dryer use an electric motor 150 w, 220v, 50 / 60Hz, 1.35A. This machine will work when the motor is energized so that this motor will rotate the pulley at the end of the motor shaft. The pulley rotation will be continued by the V belt (V-Belt) so that it rotates the attached pulley.